2001
DOI: 10.1148/radiology.219.1.r01ap0695
|View full text |Cite
|
Sign up to set email alerts
|

Early Prediction of Irreversible Brain Damage after Ischemic Stroke at CT

Abstract: After ischemic stroke, x-ray hypoattenuation at CT is highly specific for irreversible ischemic brain damage if detection occurs within the first 6 hours. Patients without hypoattenuating brain tissue have a more favorable clinical course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
172
0
12

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 310 publications
(191 citation statements)
references
References 30 publications
7
172
0
12
Order By: Relevance
“…Our results confirm the generally accepted notion that in acute cerebral ischemia, regions of hypoattenuation on noncontrast CT and CTA source images and hypoperfusion on CT perfusion CBV maps represent unsalvageable tissue despite reperfusion. 19,20 However, in the 3-hour window, CBV appears to be a significantly more sensitive and accurate marker for irreversible ischemic damage. We compared the mean ASPECTS of each CT-based technique and found no difference between the scores on noncontrast CT and CTA source images, but both were different from scores on CT perfusion CBV maps.…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirm the generally accepted notion that in acute cerebral ischemia, regions of hypoattenuation on noncontrast CT and CTA source images and hypoperfusion on CT perfusion CBV maps represent unsalvageable tissue despite reperfusion. 19,20 However, in the 3-hour window, CBV appears to be a significantly more sensitive and accurate marker for irreversible ischemic damage. We compared the mean ASPECTS of each CT-based technique and found no difference between the scores on noncontrast CT and CTA source images, but both were different from scores on CT perfusion CBV maps.…”
Section: Discussionmentioning
confidence: 99%
“…We defined hypodensity as a visible decrease in x-ray attenuation of brain tissue compared with the attenuation in other portions of the brain. 13 All patients or relatives gave informed consent before cerebral angiography and intra-arterial thrombolysis. Approval was granted by our institutional review board.…”
Section: Methodsmentioning
confidence: 99%
“…Our data indicate that extensive early CT signs appear in about 64% of patients with large vessel occlusions, despite arriving at the hospital and undergoing brain CT imaging within 3 hours after onset. von Kummer et al reported early CT signs in 82% of patients within 6 hours of the onset of MCA ischemic stroke, and this group did not have a good prognosis over a 3-month follow-up period after r-tPA treatment [7][8][9] . In the European Cooperative Acute Stroke Study (ECASS), Larrue et al reported a high rate of the development of hemorrhagic infarction following r-tPA treatment in patients in whom early ischemic changes had already appeared within 6 hours of the onset of symptoms, indicating that the appearance of early CT signs more than 3 hours after onset may be an indicator of a lack of viability, and also suggesting a tendency toward hemorrhage after recanalization 10) .…”
Section: Discussionmentioning
confidence: 88%